Risk-Based Waste Control in Warehouses using FMEA and FTA Methods (Case Study on CV. Roda Lintas Equator Sidoarjo) - Untung Usada M.T; Fawasyana Kusuma Istianto (Tibuana, 2022)
Companiesthat have good management are companies that can manage risks that can occur so that the level of risk that occurs can be reduced or even eliminated. The risks that may occur can be managed by tracing beforehand so that information is obtained about the causes of these risks, and the analysis of risk assessment in the company serves as loss mitigation which will later be able to find out about the risks that will occur, the causes of the risks, the impact of these risks. as well as repair solutions to reduce waste in the warehouse. The risk assessment or risk assessment is carried out by the management, especially the head of the warehouse. The data obtained were then analyzed using the Failure Mode and Effects Analysis (FMEA) method and the Fault Tree Analysis (FTA) method. The analysis generates the value of the risk level (TR), and Risk Priority Number (RPN) and details the causes of a Top Event to a root cause failure. The results of the analysis obtained 25 risks for the entire process failure with the largest RPN value, namely the damaged network connection with a value of 40.74 while the smallest RPN value, namely the risk of lack of light intensity with a value of 4.89, the risk of damage to hardware with a value of 4.89.